Performance Measurement in Corporate Governance DEA Modelling and Implications for Organisational Behaviour and Supply Chain Management - Manzoni, Alex; Islam, Sardar M. N. (Contributions to Management Science, 2009)
In the global knowledge economy, corporate governance, organisational behaviour and performance of the supply chain are becoming increasingly important aspects of the evaluation of an enterprise. The subject of this book is the development of a contemporary organisation behaviour performance measurement (OBPM) model for enterprises in the modern economy. The fields of organisation behaviour and supply chain management are integrated with an Open Socio-Technical Systems theory of management and the application of Operations Research to corporate governance for the measurement of organisation performance. This book thereby offers a new and innovative quantitative approach to qualitative concepts of corporate performance measurement and makes a significant contribution to the fields of management theory, supply chain management as well as operations research.